Eryngium corniculatum Lam. (Apiaceae) y su hábitat, novedad en la provincia de Málaga (España) - Pérez-Latorre, Andrés Vicente; Carralero Benítez, Julio (UMA Editorial, 2025)
Se ha recolectado Eryngium corniculatum como nueva cita en la provincia de Málaga (España) y segunda cita para Andalucía Oriental. Se han identificado tanto la asociación como el Hábitat de Interés Comunitario (HIC) donde habita, que constituyen primera cita para Andalucía Oriental.

Eryngium corniculatumhas been collected as a new record for Malaga province (Spain) and second record for Eastern Andalusia. The phytosociological association and the Habitat of Community Interest (HIC) where Eryngiumgrows, have been identified and both constitute a new record for Eastern Andalusia.
Eryngium corniculatumLam. (Apiaceae) and its habitat, a novelty in the province of Malaga (Spain)
Keywords: Plantas - Clasificación; Umbelales - Andalucía; Nueva cita; Umbelíferas; Isoeto-Nanojuncete; Zonas húmedas; Andalucía